2022
DOI: 10.1021/acs.organomet.2c00520
|View full text |Cite
|
Sign up to set email alerts
|

α-Methylation of Ketones and Indoles Catalyzed by a Manganese(I) PCNHCP Pincer Complex with Methanol as a C1 Source

Abstract: Acceptorless alcohol dehydrogenation is a powerful reaction in sustainable synthesis. When combined in a tandem reaction with dehydrogenative coupling or hydrogen borrowing, acceptorless dehydrogenation can be used for the environmentally benign construction of C−C, C−N, and C−O bonds. While many of these reactions rely on using precious metals, in the past decade the use of earth-abundant metals has become more prevalent. If a green and renewable feedstock could be introduced as well, the sustainability of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 78 publications
0
9
0
Order By: Relevance
“…To start with, 3 was tested as a precatalyst for the β-methylation of alcohols (Scheme ). This one-pot, three-step (i.e., sequential target alcohol/methanol dehydrogenation, cross-aldol condensation, and rehydrogenation) transformation is now well-established to be performed by both late transition metal and earth-abundant metal-based complexes. Although this reaction requires heating due to the key methanol dehydrogenation step (Δ H for methanol is +84 kJ mol –1 ), the average reaction conditions for this method rely on very high reaction temperature (often above 150 °C) even under high catalyst loading.…”
Section: Results and Discussionmentioning
confidence: 73%
“…To start with, 3 was tested as a precatalyst for the β-methylation of alcohols (Scheme ). This one-pot, three-step (i.e., sequential target alcohol/methanol dehydrogenation, cross-aldol condensation, and rehydrogenation) transformation is now well-established to be performed by both late transition metal and earth-abundant metal-based complexes. Although this reaction requires heating due to the key methanol dehydrogenation step (Δ H for methanol is +84 kJ mol –1 ), the average reaction conditions for this method rely on very high reaction temperature (often above 150 °C) even under high catalyst loading.…”
Section: Results and Discussionmentioning
confidence: 73%
“…The reaction did not proceed well without an inorganic base and catalyst (Table 1, entries 13, 14). Commercially available Zn(II)-salts such as ZnCl 2 and Zn(ClO 4 ) 2 were ineffective (Table 1, entries 22,23).…”
Section: Resultsmentioning
confidence: 99%
“…19 Our mechanistic studies indicated that initial hydride transfer from a Mn(I)-hydride complex, is responsible for the hydrogenation of the in situ formed α,βunsaturated ketone. 19 Inspired by the reactivity of the [(PC NHC P)Mn(CO) 2 H] complex (1), we envisioned that α,β-unsaturated ketones could, perhaps, also be directly hydrogenated with H 2 in a chemoselective manner. Here we report the chemoselective 1,4-reduction of α,β-unsaturated ketones under ambient pressures of hydrogen (mostly 1−2 bar H 2 ) without the need for any additional additives (Figure 1B).…”
mentioning
confidence: 77%